Does an MBA degree advance business management skill or in fact create horizontal and vertical mismatches? - Alam, Gazi Mahabubul; Parvin, Morsheda; Mohd Ayub, Ahmad Fauzi; Kader, Romana; Rahman, Md. Mahfuzur (Emerald Group Publishing, 2021)
Purpose: An old saying –“Jack of all trades, master of none”– deliberately asserts that the purpose of a master’s degree program is to generate high level job skills in order to improve a nation's economy, while a bachelor degree produces economically productive graduates. Employment of such graduates is fundamentally important for personal and economic development. There is a link between a bachelor’s and master's degree and how these qualifications are linked to the job market. Both horizontal and vertical mismatches are developed which is the central focus of this research. Design/methodology/approach: Given the differentiated nature of research questions, multiple techniques are used to collect the data. However, this research bears the norms of the qualitative method. Both secondary and primary data are used, and meanwhile secondary data are collected by the banks, Bangladesh Bureau of Educational Information and Statistics (BANBEIS), University Grants Commission (UGC) and by the institutions sampled. Primary data are gathered from interviews with key people. Data were collected from three institutions of higher education and from six commercial banks and from the Central Bank. The academic results of 21,325 MBA graduates and education backgrounds of 750 executives working in banks served as the basis for establishing our arguments. Findings: This study discovers that MBA graduates who have studied science subjects achieved much better grades in the MBA compared to their counterparts who studied business from secondary provision to first degree. The market-driven MBA programme has become a “business product”. The major revenue of higher education institutions comes from enrolment in MBA courses. For this reason, a science-friendly MBA program is developed to generate more business. If this continues, the philosophy of the master's program would either be lost or will have to be redefined in the 21st century. Originality/value: While a few studies have investigated the area of HE in Bangladesh, none covers the impact of MBA degrees on the job market and its contribution to enhancing job skills.